Epidemiology and Healthcare Resource Utilization Associated With Children With Short Bowel Syndrome in the United States. (30th October 2015) - Pant, Chaitanya; Sferra, Thomas J.; Fischer, Ryan T.; Olyaee, Mojtaba; Gilroy, Richard
Abstract : Background: There is a lack of large database research relating to the epidemiology and health resource utilization associated with short bowel syndrome (SBS) in the United States. Methods: We analyzed the Kids' Inpatient Database for the year 2012 and utilized International Classification of Diseases, Ninth Revision, and Clinical Modification ( ICD‐9‐CM ) diagnosis codes to identify patients 0–3 years of age with SBS, who were matched by age and sex to children without SBS. The study variables included patient and hospital demographics, All Patient Refined Diagnosis Related Groups, in‐hospital mortality, hospital length of stay, and hospitalization costs. We also determined the most frequent ICD‐9‐CM diagnostic and procedural codes associated with SBS. Results: Children with SBS demonstrated a higher rate of mortality than that of children without SBS (1.6% vs 0.7%; P < .001). Children with SBS also experienced a longer length of stay (median days [interquartile range]: 8 [15] vs 2 [3]; P < .001) and higher hospital costs ($17, 000 [$34, 000] vs $3000 [$5000]; P < .001). The most frequent medical diagnoses associated with SBS were infection (62%), anemia (29%), and liver disease (17%). Children with SBS also demonstrated more severe illness as assessed by an All Patient Refined Diagnosis Related Group score of 3 or 4 (94.30% vs 16.20%; P < .001). Conclusions: Children hospitalized with SBS have a high severity of illness and experience complicated inpatient courses related to their disease. Our study represents the first use of national U.S. data to study the epidemiology and health resource utilization associated with SBS.